Targeting the TGF-β Pathway to Overcome Resistance to Immune Checkpoint Inhibitors in Microsatellite Stable Metastatic Colorectal Cancer: A Systematic Review and Pooled Analysis of Efficacy and Tumor Microenvironment Modulation - Aprizal Satria; Norman Djamaludin; Yenny Dian Andayani; Mediarty Syahrir (HM Publisher, 2025)
Background: The clinical utility of immune checkpoint inhibitors (ICIs) in metastatic colorectal cancer (mCRC) is restricted to a minority of tumors with mismatch repair deficiency. The vast majority, classified as microsatellite stable (MSS), display profound resistance driven by an immunosuppressive tumor microenvironment (TME) orchestrated by transforming growth factor-β (TGF-β). This study aimed to synthesize the evidence for combining TGF-β pathway inhibitors with ICIs to reverse this resistance. Methods: A systematic search of PubMed, Embase, Cochrane Library, and major oncology conference abstracts was conducted through December 2024 for preclinical and clinical studies evaluating TGF-β inhibition combined with ICIs in CRC. Due to the non-randomized nature of the clinical evidence, a pooled analysis of the single-arm objective response rate (ORR) was performed using a random-effects model. Progression-free survival (PFS), duration of response (DoR), and TME modulation were synthesized narratively. Results: Seven studies (four preclinical, three early-phase clinical) met the inclusion criteria. In the pooled analysis of 218 patients with predominantly MSS-mCRC from three clinical trials, the combination therapy yielded a pooled ORR of 14.2% (95% Confidence Interval [CI]: 9.1% – 20.2%), with moderate heterogeneity (I² = 38%). This represents a clinically meaningful improvement over the expected <1% response rate to ICI monotherapy in this population. Narrative synthesis of survival data indicated a median PFS ranging from 2.5 to 3.7 months and a promising median DoR exceeding 10 months in responders. Preclinical data consistently demonstrated that combination therapy synergistically inhibited tumor growth by remodeling the TME, marked by increased CD8+ T-cell infiltration and reduced stromal fibrosis. Conclusion: This systematic review and pooled analysis provide the most current synthesis of evidence for targeting the TGF-β pathway in MSS-mCRC. While preliminary and based on early-phase trials, the data show that this combination strategy can induce durable responses in a subset of patients by promoting an inflamed TME. These findings strongly support the continued investigation of this approach in biomarker-driven, randomized controlled trials.